Clinical profile of typhoid fever in children at a tertiary care hospital: a cross sectional study - S. S., Siddiqui; Koppa, Shivraj Kumar; A. V., Kale (International Journal of Contemporary Pediatrics, 2017)
Background: In endemic areas such as India, traditional signs and symptoms in enteric fever are not often observed. Unusual presentations lead to diagnostic dilemma and may delay the diagnosis of typhoid fever. The present study describes the clinical presentation of enteric fever at a tertiary care centre in Aurangabad district of Maharashtra. Methods: The study was a hospital based prospective observational study done in paediatric ward of MGM Medical College, Aurangabad over a period of 18 month starting from 1st November 2013 to 31st April 2015. The parents of the children were informed about the research and its objectives, and written informed consent was obtained from them. Prior approval was taken from institutional ethics committee. Children of age 2 -18 years who presented with fever of 5 days or more with clinical signs and symptoms suggestive of typhoid fever and positive Widal test or Typhidot tests were included in the study. The demographic and clinical features of the patients were described. Results: Total of 99 patients were included in the study. Majority of the children were between 2 - 7 year age group (45.4%). Out of 99 children, 57 were males and 42 were females. Majority of the cases were from urban areas accounting for 75%, which included urban slums. Drinking water source was tap water in 80% cases and bore well water in 20% cases. Only 36.4% of children had fever of less than one-week duration. 58.6% of the cases had fever of more than one week but less than two weeks. Continuous fever was noticed in majority of children (55.55%). All the children presented with fever as the main complaint (100%). Loss of appetite and headache were the next common complaints reported by 59.6% cases. Commonest sign noticed was toxic look (83.8%) followed by coated tongue (74.7%) and splenomegaly (61.6%). Hepatomegaly was also noted in 39.4% of cases. Conclusions: Clinical presentation in the study subjects was similar to available reports from literature.